Acute obstructive cholangitis due to fishbone in the common bile duct: a case report and review of the literature - Yu, Min; Huang, Bowen; Lin, Ye; Nie, Yuxue; Zhou, Zixuan; Liu, Shanshan; Hou, Baohua (BMC gastroenterology, 2019)
Choledocholithiasis is an endemic condition in the world. Although rare, foreign body migration with biliary complications needs to be considered in the differential diagnosis for patients presenting with typical symptoms even many years after cholecystectomy, EPCP, war-wound, foreign body ingestion or any other particular history before. It is of great clinical value as the present review may offer some help when dealing with choledocholithiasis caused by foreign bodies. We reported a case of choledocholithiasis caused by fishbone from choledochoduodenal anastomosis regurgitation. Moreover, we showed up all the instances of choledocholithiasis caused by foreign bodies published until June 2018 and wrote the world's first literature review of foreign bodies in the bile duct of 144 cases. The findings from this case suggest that the migration of fishbone can cause various consequences, one of these, as we reported here, is as a core of gallstone and a cause of choledocholithiasis. The literature review declared the choledocholithiasis caused by foreign bodies prefer the wrinkly and mainly comes from three parts: postoperative complications, foreign body ingestion, and post-war complications such as bullet injury and shrapnel wound. The Jonckheere-Terpstra test indicated the ERCP was currently the treatment of choice. It is a very singular case of choledocholithiasis caused by fishbone, and the present review is the first one concerning choledocholithiasis caused by foreign bodies all over the world.